1881 Kan. Sess. Laws §§1, 23, pp. 79, 92 - (:unkn) unknown (General Publisher, 1881)
Mandated that the Council shall prohibit and punish the carrying of firearms, other dangerous and deadly weapons.
--
Keywords: CARRY